The Correlation betwen housewife's level of knowledge and their behaviour in responding to hoaxs news: HUBUNGAN TINGKAT PENGETAHUAN IBU RUMAH TANGGA TERHADAP PERILAKU MENANGGAPI BERITA HOAX PADA MEDIA WHATSAPP DI KECAMATAN TENJOLAYA KABUPATEN BOGOR - Muslikhah, Febri Palupi; Amalia, Nurul (JURNAL KOMUNITAS, 2024)
by social media. Whatsapp as a social media is the largerst users, which 56% of them are 25 years and over. Meanwhile Kominfo survey stated that 52,5 % internet users admitted they did not first check the truth of news that they received from social media.The purpose of this study was to determine the relationship between housewife knowledge level in responding to hoax news via WhatsApp media in Bogor and how big the relationship is. The method used is correlation with Rank Spearman analysis. The study involved 96 samples from 2479 populations based on the Simple Random Sampling technique and used a Likert scale questionnaire in collecting data. The results of the study show that 1) There is a relationship between media literacy of housewives in responding to hoax news via WhatsApp media based on a Sig value of 0.000 < ɑ 0.1. 2) Has a strong relationship with the Correlation Coefficient value of 0.536** and is included in a positive relationship, that is, when the knowledge of housewives is good, response to hoax news is also good, and when the knowledge level of housewives is not good so responding to hoax news is also not good.